O homem como promessa: estudo das implicações da antropologia filosófica de P. Ricoeur - João Batista Botton (2017)
Our research investigates the notion of promise in Paul Ricoeur's work as one of the apexes of his philosophical anthropology. Through it it's explored the main consequences for the concept of person. We hold that the compromising component of the promise develops a poignant indeterminacy: the promise is affirmed as a way of redemption of will by the element of initiative that it involves, at the same time as, specifically, this compromising component, binds the individual to a course of action fixed by the moral obligation to keep the word once committed. This ambiguity is often exploited by the service of narrative experiments (the filmic and literary narrative), which brings into play the compromising element of action, allowing us to consider that between a type of "nihilism" resulting from the first ambiguity of the promise and "fundamentalism " demanded by the second, the action demands from the narrative models to configure the construction of practical-value scales in which the polysemy is safeguarded that allows the controlled renovation of our moral concepts.